2022
DOI: 10.3389/fcell.2022.932510
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer cells of increasing metastatic potential exhibit diverse contractile forces, cell stiffness, and motility in a microenvironment stiffness-dependent manner

Abstract: During metastasis, all cancer types must migrate through crowded multicellular environments. Simultaneously, cancers appear to change their biophysical properties. Indeed, cell softening and increased contractility are emerging as seemingly ubiquitous biomarkers of metastatic progression which may facilitate metastasis. Cell stiffness and contractility are also influenced by the microenvironment. Stiffer matrices resembling the tumor microenvironment cause metastatic cells to contract more strongly, further pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…However, PC3 and DU145 cells expressed more exosomal PD‐L1 than LNCaP and 22RV1 cells (Figure 1C). It is important to note that PC3 and DU145 cells are more aggressive than the latter two types 25,26 . Immunofluorescence staining revealed that PD‐L1 co‐localized with a well‐established exosome marker (CD63) in PC3 and DU145 cells (Figure 1D,E).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, PC3 and DU145 cells expressed more exosomal PD‐L1 than LNCaP and 22RV1 cells (Figure 1C). It is important to note that PC3 and DU145 cells are more aggressive than the latter two types 25,26 . Immunofluorescence staining revealed that PD‐L1 co‐localized with a well‐established exosome marker (CD63) in PC3 and DU145 cells (Figure 1D,E).…”
Section: Resultsmentioning
confidence: 97%
“…It is important to note that PC3 and DU145 cells are more aggressive than the latter two types. 25 , 26 Immunofluorescence staining revealed that PD‐L1 co‐localized with a well‐established exosome marker (CD63) in PC3 and DU145 cells (Figure 1D,E ). Taken together, these data suggest that exosomal PD‐L1 is widely present in prostate cancer cell lines and increases in more malignant cells.…”
Section: Resultsmentioning
confidence: 99%
“…To closely emulate native settings, we indeed cultured cells on ECM-coated substrates and controlled near-native stiffness conditions EMT and cellular force generation are believed to be closely correlated. For example, metastatic/mesenchymal cancer cells of different tumor types (prostate, breast and lung) showed higher contractile forces [7,12] compared to non-metastatic phenotypes. The correlation between EMT and traction forces in PDAC was first investigated by Nguyen and collaborators, who reported that in PDAC the metastatic potential does not correlate with increased traction forces [5].…”
Section: Discussionmentioning
confidence: 99%
“…Cellular mechano-transduction, the process by which mechanical cues are converted into intracellular molecular signals, along with interactions with the surrounding extracellular matrix (ECM) play a pivotal role in cell homeostasis and signaling. Increasing evidence show that this phenomenon is particularly critical in cancers that develop abnormal ECM, causing tumor progression, increased metastatic potential and drug resistance [5][6][7]. PDAC is characterized by a drastic change in the ECM reflected by tissue stiffening.…”
Section: Introductionmentioning
confidence: 99%
“…However, PCa appears to deviate from the cell-softening trends described in other cancer models, in which with the increasing of stiffness of PCa cells, the metastasis potential is also increasing [ 49 53 ]. In addition, a recent study found that the cell and tissue mechanic characteristics of different metastatic potential cells were diverse, which meant the relationship between the metastatic ability and membrane tension and tissue stiffness of PCa cells was not necessarily linear [ 54 ]. These confounding results indicate that microenvironment mechanics are a significant yet nuanced factor in the progression of PCa.…”
Section: Discussionmentioning
confidence: 99%